Leadership Perspectives on Emotional Labour in Large Urban Public Libraries - Rodger, Joanne; Erickson, Norene (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
The demands of public library work have intensified, placing strain on both frontline staff and the leaders responsible for supporting them. Emotional labour—the regulation of emotions required in daily work—remains underexplored in library and information sciences research, particularly regarding how leaders manage their own emotional labour while supporting frontline staff. This study examines what library leaders know about emotional labour and how that knowledge influences their leadership and support for staff. Interviews with 27 leaders from three large Canadian public libraries reveal that leaders play a crucial role as middle managers, balancing staff well-being with organizational expectations. As authentic leaders, they strive to build meaningful emotional connections with their teams—often successfully—but at a personal cost. Despite their dedication, they have limited power to address systemic challenges such as precarious work, chronic understaffing, and the increasing pressure of societal issues, all of which intensify emotional labour demands. Addressing these challenges requires a collective effort. Libraries must adopt a proactive approach to emotional labour, emphasizing leadership development, shared responsibility, and comprehensive organizational support.